S and G(2) Phase Roles for Cdk2 Revealed by Inducible Expression of a Dominant-Negative Mutant in Human Cells - Hu, Bing (American Society for Microbiology, 2001)
Cyclin-dependent kinase 2 (Cdk2) is essential for initiation of DNA synthesis in higher eukaryotes. Biochemical studies in Xenopus egg extracts and microinjection studies in human cells have suggested an additional function for Cdk2 in activation of Cdk1 and entry into mitosis. To further examine the role of Cdk2 in human cells, we generated stable clones with inducible expression of wild-type and dominant-negative forms of the enzyme (Cdk2-wt and Cdk2-dn, respectively). Both exogenous proteins associated efficiently with endogenous cyclins. Cdk2-wt had no apparent effect on the cell division cycle, whereas Cdk2-dn inhibited progression through several distinct stages. Cdk2-dn induction could arrest cells at the G(1)/S transition, as previously observed in transient expression studies. However, under normal culture conditions, Cdk2-dn induction primarily arrested cells with S and G(2)/M DNA contents. Several observations suggested that the latter cells were in G(2) phase, prior to the onset of mitosis: these cells contained uncondensed chromosomes, low levels of cyclin B-associated kinase activity, and high levels of tyrosine-phosphorylated Cdk1. Furthermore, Cdk2-dn did not delay progression through mitosis upon release of cells from a nocodazole block. Although the G(2) arrest imposed by Cdk2-dn was similar to that imposed by the DNA damage checkpoint, the former was distinguished by its resistance to caffeine. These findings provide evidence for essential functions of Cdk2 during S and G(2) phases of the mammalian cell cycle.